Capital market seasonality: The case of stock returns - Rozeff, Michael S.; Kinney, William R. (Journal of Financial Economics, 1976)
In this paper we present evidence on the existence of seasonality in monthly rates of return on the New York Stock Exchange from 1904–1974. With the exception of the 1929–1940 period, there are statistically significant differences in mean returns among months due primarily to large January returns. Dispersion measures reveal no consistent seasonal patterns and the characteristic exponent seems invariant among months. We also explore possible implications of the observed seasonality for the capital asset pricing model and other research.